Identification and control of Occupational Health and Safety (OHS) risks in the slope and drainage reinforcement project on the Paksebali – Selat Provincial Road Section - I Nyoman Indra Kumara; I Gede Agus Suparta; I Komang Agus Ariana; I Gede Fery Surya Tapa (Privietlab, 2026)
The slope and drainage reinforcement project on the Paksebali–Selat Provincial Road section involves a relatively high potential for Occupational Health and Safety (OHS) risks due to excavation works, concrete casting, the use of heavy equipment, and hazardous working environment conditions. This study aims to identify extreme and high risks that may lead to work accidents and to determine appropriate OHS risk control measures for the project. The research method employed is a quantitative descriptive approach, with data collected through field observations, interviews, questionnaires, and documentation studies. Risk assessment was conducted based on the AS/NZS 4360 standard by multiplying the probability and severity levels, whereas risk control was analyzed using the Plan–Do–Check–Act (PDCA) cycle approach. The results indicated that the risks identified in this project fell into the extreme and high-risk categories, particularly in excavation works, road shoulder concrete casting, and heavy equipment mobilization. Potential hazards included landslides, being struck by equipment, and accidents caused by improper work methods. Risk control measures were implemented through improvements in work methods, enforcement of Personal Protective Equipment (PPE) usage, enhanced supervision, installation of safety signs, and the regular implementation of training and safety meetings. The application of appropriate risk control measures is expected to minimize workplace accidents and improve overall project safety performance.